Case study: The Met Office. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – This case study aims to discuss how the Met Office developed a process for creating ideas that help people look at markets differently and bring people with diverse knowledge together to generate better ideas. The Met Office is the UK's national weather service and an arm of the Department for Business Innovation and Skills. In its 160 years of history, it has been part of a number of Government Departments, including the Board of Trade, the Air Ministry and the Ministry of Defence, where it became an executive agency with a remit to act commercially. Design/methodology/approach: – Creating and maintaining income streams in a competitive international market requires ongoing innovation and while its long history and sector pre-eminence means the Met Office has always been successful, it is not always easy to innovate in a public sector organisation with an ingrained culture and traditional top-down authority structure. Findings: – This case study discusses how the Met Office developed a process for creating ideas that help people look at markets differently and bring people with diverse knowledge together to generate better ideas. Originality/value: – Inspired by external influence, a small core of innovators began a process of "guerrilla" tactics to drive the process forward, firstly by visiting other businesses including Google and Innocent and learning from the experiences they found there. This included Google's concept of "Playtime" (allowing people some freedom to play with their pet products) and the use of kitchens to encourage employee interaction. The case study concludes with observations for others to consider in the process of introducing employee-led innovation.